Two-Phase Flow in Circular Secondary Sedimentation Tanks - Matko, T. I. R. (Cranfield University, 1997)
The main objective of this work was to optimise a numerical model to predict the flow in circular secondary sedimentation tanks. The numerical models in the literature were reviewed and the new opportunities for research were identified. Single-phase flow characteristics of two circular sedimentation tanks were investigated using the CFD program, CFX-F3D. The flow in the circular clarifiers were modelled in two dimensions (axial and radial) and using the standard k-E turbulence model. Results indicated that a vertical inlet instead of a horizontal inlet did not improve the correlation with the experimental data in a pilot-scale tank. Modelling the diurnal variation in flow to a full-scale tank significantly improved the correlation with experimental data. The `Eulerian multi-fluid' model in the program, CFX-F3D was modified to predict the flow in circular secondary sedimentation tanks. The model compared quite closely with the measured residence time of the effluent and return activated sludge (RAS) in a conventional secondary clarifier. The residence time of the effluent in another secondary clarifier with a turbulent jet, was over-predicted. The mean particle diameter in the model was found by comparing the numerical predictions with experimental data. The particle diameter was between 100 to 190 μm for the secondary clarifiers, which was in agreement with the experimental data in the literature. The flow patterns in the conventional secondary clarifier were affected by the particle density, particle diameter, axial slip velocity, colloids settling parameter, axial turbulent Prandtl number, inlet flow rate and inlet solids concentration. A 3-D simulation of the conventional secondary clarifier was in agreement with a 2-D simulation. Recommended values were given for all these parameters. However, the drag force between the phases was not formulated correctly and the water surface was modelled as a symmetry plane. Therefore, some more work is still required to make suitable modifications to the model.